Unlicensed to Prescribe Herbs: A Chinese Healer – Médico Chino – in Puerto Rico, 1851-1853 - Rigau-Pérez, José G. (Puerto Rico Health Sciences Journal, 2016)
In Puerto Rico and Cuba, the phrase “can’t be saved even by the Chinese physician” (“no lo salva ni el médico chino”) indicates a person with an incurable disease. The documents at the Archivo General de Puerto Rico include three requests for a medical license from a Chinese immigrant, Juan de Dios Sian (Lin Hua Cheng). Despite lacking legal credentials, he used herbal therapies to treat chronically ill persons in Ponce, San Juan and Mayaguez from 1851 to 1853. Before arriving in Ponce he had spent four years in Cuba, where he is again found by 1865. Sian’s petitions show that Puerto Rico, like Cuba, experienced a widely known “médico chino.” The anecdote reminds us of important issues in our medical and social history: Asiatic immigration (earlier, larger and more diverse than usually considered), access to care (and its limitations), and the long history of herbal medicine in Oriental and Western cultures. Elements of this story, such as the eagerness for new treatments among patients who have derived no benefit from standard therapy, the ethics of medical licensing, the impotence of licensing agencies and the toleration of authorities regarding an unorthodox but popular healer, exemplify dilemmas that accompany medical practice at all times.